The Emperor Nero : a guide to the ancient sources - Barrett, Anthony, 1941-; Fantham, Elaine; Yardley, John, 1942- (Princeton University Press, 2016)
Nero's reign (AD 54-68) witnessed some of the most memorable events in Roman history, such as the rebellion of Boudica and the first persecution of the Christians - not to mention Nero's murder of his mother, his tyranny and extravagance, and his suicide, which plunged the empire into civil war. This book gathers into a single collection some of the major sources for Nero's life and rule, providing students of Nero and ancient Rome with the most authoritative and accessible reader there is. The book features clear, contemporary translations of key literary sources along with translations and explanations of representative inscriptions and coins issued under Nero. An informative introduction situates the emperor's reign within the history of the Roman Empire, and concise headnotes to chapters place the source material in historical and biographical context. Passages are accompanied by detailed notes and are organized around events, such as the Great Fire of Rome, or by topic, such as Nero's relationships with his wives. Complex events like the war with Parthia - split up among several chapters in Tacitus - are brought together in continuous narratives, making this one of the most comprehensible and user-friendly sourcebooks on Nero.